The Role of Physical Activity in Pregnancy: Impact on Preeclampsia, Gestational Diabetes Mellitus, and Labor Outcomes - Woźniak, Paulina; Wietrzykowska, Ewa; Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Wirkijowska, Małgorzata; Wirkijowski, Jakub; Wójtowicz, Katarzyna; Walczak, Agata; Sobolewska, Dominika; Michalczyk-Fraszka, Katarzyna; Śliwińska, Martyna; Podraza, Anna (Journal of Education, Health and Sport, 2025)
Physical activity (PA) is of crucial importance when aiming to maintain a healthy lifestyle. Pregnancy is a period in which many hormonal and physiological changes occur, sometimes leading to development of diseases such as gestational diabetes (GDM) and preeclampsia. In this systematic review the influence of regular PA both before and during gestation is investigated. The research gathered points towards the preventive nature of PA against GDM and preeclampsia, proving that regular exercise, especially of moderate and moderate-to-vigorous intensity, significantly reduces the risk of the development of both of these. Additionally, women with GDM treated with insulin who regularly participate in PA require a lower dosage compared to those leading sedentary lifestyles. On top of that, PA seems to have a beneficial influence on various labor outcomes, such as shortened active labor duration, lowered reported levels of pregnancy-related pain, improved psychological well-being, and increased chances of natural vaginal birth as opposed to cesarean section or instrumental birth.